Historical and Contemporary Uses of Sea Buckthorn, Hippophae rhamnoides L., in the Nordic Countries - Ståhlberg, Sabira; Svanberg, Ingvar (Journal of Northern Studies, 2022)
Human interest in certain plants can vary considerably over time. At the end of the twentieth century, the orange-yellow fruits of sea buckthorn, Hippophae rhamnoides Linnaeus, became a trendy addition to the diet in some Nordic countries, especially in Sweden and Finland. The soft and juicy fruits are very rich in vitamin B12, C and E, and this fact has greatly contributed to its popularity among contemporary healthconscious consumers. As a cultivated plant, it is nowadays suitable also for a colder climate, and yields an abundant harvest. In pre-industrial times, the sour-tasting sea buckthorn berries were rarely harvested, although some examples are known from older sources. In 1732, Carl Linnaeus recorded that the berries were used to make a kind of simple sauce served with fish along the Swedish coast of the Gulf of Bothnia. In the nineteenth century, increasing availability of sugar made it possible to consume and preserve the berries on a larger scale, and today they are used in confectionery, cordial, ice-cream, jam, juice, marmalade, mash, parfaits, smoothies, sweets, beer, yogurt products and hygiene products (shampoo and soap). This article discusses how a rather unknown wild shrub, mostly unnoticed in peasant folk botany along the northern European coasts, has become common as a cultivated plant. Sea buckthorn is a classic example of how the interest in a particular plant and its edible parts varies over time due to economic, cultural and social changes. Ethnobiologist must study not only the human-plant relationships (folk knowledge and utilisation) in the specific socio-cultural context, but also answer questions about how a plant was utilised and viewed, when, where and by whom, as well as why.